A calculation method of interior ballistic two-phase flow considering the compression and fracture process of propellant bed. (June 2020) - Zhang, Ruihua; Rui, Xiaoting; Li, Chao; Wang, Yan; Zhao, Xin; Dong, Xiaoli
Abstract: The fracture degree of propellant charge on the projectile base before it is ignited is the key to study the launch safety of propellant charge and simulate the breech-blow phenomenon of the gun. In this paper, by solving the difficult problem of calculating the gas generation law of fractured propellant charge, an interior ballistic two-phase flow calculation method with mixed-charge considering the fractured propellant charge is established. Through the test method for mechanical situation of propellant charge, the time history of compression stress of propellant charge near the projectile base is acquired, which is loaded into the propellant bed model based on discrete element method(DEM). The compression and fracture process of propellant charge in the 30 mm area near the projectile base at low temperature is simulated. Then the corresponding fractured propellant charge is obtained, and next setting it as the initial condition of the interior ballistic two-phase flow calculation; moreover, the simulation of interior ballistic two-phase flow with mixed-charge considering fractured propellant charge is carried out. And the simulation results are in good agreement with the ballistic performance test results. The research in this paper provides a precise calculation method for the abnormal pressure in chamber caused by fractured propellant charge, which can be used to predict the breech-blow phenomenon of the gun and to guide the design of gun charge structure. Highlights: An interior ballistic two-phase flow calculation method considering the fractured propellant charge is established. The test for mechanical situation of propellant charge is conducted. The dynamic compression and fracture simulation of the 30 mm propellant bed is simulated. Numerical simulation of interior ballistic is carried out considering fractured propellant charge.